DASAR PERTIMBANGAN PENEMPATAN MAGANG BAGI CALON NOTARIS DI KOTA SURAKARTA - , INTAN WULANSARI, Sigid Riyanto, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to determine whether based on considerations internship placement for candidates Notary Public by INI in Surakarta and the constraints internship placement for candidates Notary Public by INI in Surakarta. The method of research is empirical juridical, by examining the primary data and secondary data were analyzed in a qualitative. The conclusion to be done by method of inductive thinking. Based on usage of this method is expected to obtain obvious and comprehensive descriptions about suitability of conceptual basis that is use with the research tittles. The internship as one of requirements removal of Notary Public. The internship are very important because by internship the candidates Notary Public getting knowledges, experiences, skills, and good character to be able to excute the office of Notary Public professionally. Based on results of research and discussions of problems in this research, based on considerations internship placement for candidates Notary Public by INI that is, the membership Notary Public who is under the auspices of the INI, had been practicing for 5 (five) years and not within controls.